Introductory statistics - Mann, Prem S. (John Wiley and Sons, Inc., 2013)
Introductory Statistics is written for a one or two semester first course in applied statistics and is intended for students who do not have a strong background in mathematics. The only prerequisite is knowledge of elementary algebra. Introductory Statistics is known for its realistic examples and exercises, clarity and brevity of presentation, and soundness of pedagogical approach.